Life on the Wire—Plant Growth on Power Lines in the Americas - Zotz, Gerhard (2024)
There are a number of rather anecdotal reports of plant growth on power cables in the Americas, but until now there has been no systematic attempt to gauge the geographical extension of this phenomenon nor a documentation of the diversity of species found there. Using observations from the participatory science data platform iNaturalist and the scientific literature, we document almost 700 occurrences of more than 40 species of vascular plants and three lichen species on power cables with a geographical distribution over 7000 km from the southern United States to northern Argentina. Based on these observations we discuss the ecological conditions of plant growth on power cables in terms of climate; elevational distribution; and the morphological, physiological, and life history traits that allow the observed set of species to thrive on this anthropic structure.